Virtual Prediction of Lycopene and Quercetin Effects on Angiogenesis Through VEGFR-2 Pathway - Samoedra, Rizky Senna; Sari, Fikriya Novita; Pratama, Setyaki Kevin (JSMARTech: Journal of Smart Bioprospecting and Technology, 2020)
Angiogenesis is a complex process that is required for cancer cells to perform metastasis. The binding of a growth factor such as VEGF to its receptor is one of the factors to trigger angiogenesis through VEGFR-2 pathway. This study is conducted to analyze the effect of lycopene and quercetin, which are compounds found in watermelon (Citrullus lanatus) on angiogenesis through VEGFR-2 pathway. The study was carried out in silico. Ligands were obtained from PubChem and prepared using PyRx while the protein was obtained from PDB and prepared using BIOVIA Discovery Studio 2019. The docking was done by using HEX 8.0.0 and the results were visualized using BIOVIA Discovery Studio 2019. Lycopene and quercetin were able to bind with VEGFR-2 to interrupt the binding of VEGFA. The presence of lycopene and quercetin also lowers the binding strength of VEGFA with VEGFR-2 as they can affect interactions between VEGFA and VEGFR-2 at 4 and 5 amino acid residues by changing the type of interactions to make the binding strength weaker. The binding of lycopene and quercetin have the potential to interrupt the downstream pathway of angiogenesis through VEGFR-2 pathway.